Effect of heat-treated tea water-insoluble protein nanoparticles on the characteristics of Pickering emulsions. (September 2021) - Ren, Zhongyang; Chen, Zhongzheng; Zhang, Yuanyuan; Lin, Xiaorong; Li, Zhanming; Weng, Wuyin; Yang, Hongshun; Li, Bin
Abstract: Tea water-insoluble protein nanoparticles (TWIPNs) can be used as Pickering particles. However, Pickering emulsions stabilized by heat-treated TWIPNs (TWIPNPEs) were not characterized clearly. Therefore, the effect of heat-treated TWIPNs on the characteristics of Pickering emulsions was analyzed. TWIPNs became small at 60 °C and reassembled at 100 and 120 °C. Disulfide bonds and noncovalent bonds synergistically participated in the intermolecular forces of heat-treated TWIPNs. The random coil content of heat-treated TWIPNs decreased from 0.24 to 0.13 and the contents of α-helices and β-sheets increased from 0.11 to 0.27 to 0.19 and 0.30 in the proportion of secondary structure with the increase in heat-treated TWIPN temperature. High temperature (100 °C/120 °C) on TWIPN accelerated the flocculation of emulsion droplets. A potential mechanism for the changes occurring in TWIPNPEs based on heat-treated TWIPNs was proposed to exhibit the instability of TWIPNPEs stabilized by heat-treated TWIPNs due to the structural rearrangements and enhanced intermolecular forces of TWIPNs at 100 and 120 °C. Besides, heat-treated TWIPNs at 30 and 40 g/L decreased the gel-like behavior of TWIPNPEs. These results can broaden our understanding of the characteristics of TWIPNPEs stabilized by heat-treated TWIPNs for utilizing tea by-products. Highlights: TWIPNs became small at 60 °C and reassembled at 100 and 120 °C. Disulfide/noncovalent bonds in intermolecular forces of heat-treated TWIPNs. Contents of α-helices and β-sheets of TWIPNs increased with increasing temperature. Flocculation of TWIPNPEs prepared using TWIPNs at 100 and 120 °C increased. Heat-treated TWIPNs at 30 and 40 g/L decreased gel-like behavior of TWIPNPEs.